2011
DOI: 10.1165/rcmb.2011-0007oc
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Cyclophilins in the Chronic Phase of Asthma Reduces the Persistence of Leukocytes and Disease Reactivation

Abstract: Allergic asthma is characterized by acute influxes of proinflammatory leukocytes in response to allergen stimulation, followed by quiescent (chronic) periods between allergen challenges, during which sustained, low-level inflammation is evident. These chronic phases of disease are thought to be mediated by populations of leukocytes persisting within airways and tissues. The lack of any in situ proliferation by these cells, along with their limited lifespan, suggests that a continual recruitment of leukocytes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 48 publications
(62 reference statements)
2
28
0
Order By: Relevance
“…CD147 is a type I transmembrane glycoprotein, a member of the immunoglobulin super-family, that is expressed by a wide array of cell types, including epithelial, endothelial and hematopoietic cells (6). CD147 is a signaling receptor for extracellular cyclophilins (Cyp) A and B (7,8), and recent publications have identified the CD147 signaling pathway induced by extracellular cyclophilins as a triggering mechanism regulating MMP expression and inflammation in atherosclerosis, rheumatoid arthritis, allergic and chronic lung disease (9)(10)(11)(12)(13)(14). Thus, we hypothesized that CD147 activation by extracellular cyclophilin may play a role in experimental BA as well.…”
Section: Targeting Extracellular Cyclophilins Ameliorates Disease Promentioning
confidence: 99%
“…CD147 is a type I transmembrane glycoprotein, a member of the immunoglobulin super-family, that is expressed by a wide array of cell types, including epithelial, endothelial and hematopoietic cells (6). CD147 is a signaling receptor for extracellular cyclophilins (Cyp) A and B (7,8), and recent publications have identified the CD147 signaling pathway induced by extracellular cyclophilins as a triggering mechanism regulating MMP expression and inflammation in atherosclerosis, rheumatoid arthritis, allergic and chronic lung disease (9)(10)(11)(12)(13)(14). Thus, we hypothesized that CD147 activation by extracellular cyclophilin may play a role in experimental BA as well.…”
Section: Targeting Extracellular Cyclophilins Ameliorates Disease Promentioning
confidence: 99%
“…For example, Satoh et al (2013) reported that CyPA expression is significantly higher in the atherosclerotic plaque of arterial walls in patients with atherosclerosis. Additionally, Stemmy et al (2011) revealed a higher concentrations of extracellular CyPA in the chronic phase of asthma using a murine model. Billich et al (1997) found that CyPA levels were increased in the synovial fluids of patients with rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 93%
“…Many of previous studies have clearly indicated that an overexpression of CyPA is correlated with poor outcomes in patients with inflammatory diseases (Stemmy et al 2011). During the inflammation process, CyPA exacerbates oxidative stress and inflammation .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations